2018
DOI: 10.1111/ejn.13911
|View full text |Cite
|
Sign up to set email alerts
|

Atypical audiovisual temporal function in autism and schizophrenia: similar phenotype, different cause

Abstract: Binding across sensory modalities yields substantial perceptual benefits, including enhanced speech intelligibility. The coincidence of sensory inputs across time is a fundamental cue for this integration process. Recent work has suggested that individuals with diagnoses of schizophrenia (SZ) and autism spectrum disorder (ASD) will characterize auditory and visual events as synchronous over larger temporal disparities than their neurotypical counterparts. Namely, these clinical populations possess an enlarged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 90 publications
5
57
2
Order By: Relevance
“…The initial bias seemingly stemmed from a speed prior (Stocker & Simoncelli, 2006;Petzschner & Glasauer, 2011;Lakshminarasimhan et al, 2018) biasing estimates of self-velocity, and not from the leaky integration of velocity into position estimates (Mittelstaedt & Glasauer, 1991;Lappe et al, 2007Lappe et al, , 2011. Thus, the first conclusion of this work is that, contrary to what has been suggested in some previous literature (e.g., Noel et al, 2018;Iarocci & McDonald, 2006), individuals with ASD do not appear to be particularly poor integrators, at least not within the cadre of a naturalistic task wherein the integration is across a sustained time-period on the order of 5-6 seconds. This finding is in line with Giovanni et al, 2009, who demonstrated no difference between children with ASD and control individuals in blindly navigating toward a briefly presented target, using nothing but proprioceptive and kinematic information (as opposed to visual flow here).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The initial bias seemingly stemmed from a speed prior (Stocker & Simoncelli, 2006;Petzschner & Glasauer, 2011;Lakshminarasimhan et al, 2018) biasing estimates of self-velocity, and not from the leaky integration of velocity into position estimates (Mittelstaedt & Glasauer, 1991;Lappe et al, 2007Lappe et al, , 2011. Thus, the first conclusion of this work is that, contrary to what has been suggested in some previous literature (e.g., Noel et al, 2018;Iarocci & McDonald, 2006), individuals with ASD do not appear to be particularly poor integrators, at least not within the cadre of a naturalistic task wherein the integration is across a sustained time-period on the order of 5-6 seconds. This finding is in line with Giovanni et al, 2009, who demonstrated no difference between children with ASD and control individuals in blindly navigating toward a briefly presented target, using nothing but proprioceptive and kinematic information (as opposed to visual flow here).…”
Section: Discussioncontrasting
confidence: 81%
“…to be either negative or positive (or zero; flat prior). In addition, as many (Rinehart et al, 2000;Iarocci et al, 2006;Robertson et al, 2012;Stevenson et al, 2014;Noel et al, 2018) claim that individuals with ASD are poor integrators, we also fit a leaky integrator model, where the prior was held flat ( ! = !…”
Section: Model Fittingmentioning
confidence: 99%
“…In function (1), the mean of the best-fitting distribution was taken as a measure of PSS and the standard deviation was taken as the TBW [Noel, Lytle, Cascio, & Wallace, 2018;Noel, Stevenson, & Wallace, 2018]. The amplitude was free to vary and could exceed 1.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, back fitting data to these models allows extrapolating latent variables, such as the prior probability of attributing common cause to multisensory signals given certain stimuli properties, not directly measurable in the brain or through behavior without a model (see Ref. ). Interestingly, recent work has combined a modeling approach incorporating Bayesian priors with direct auditory recordings of the environment to suggest that, in fact, as suggested by early physiological recordings, the nervous system adapts (developmentally, but inclusively evolutionarily) to the statistical regularities of the external world .…”
Section: Multisensory Integrationmentioning
confidence: 99%
“…In turn, the priors reflect accumulated history of sensory likelihoods, and hence if low‐level sensory processing is altered, over the course of many exposures, priors—cognition—will be distorted as well. Fittingly, multisensory integration is well documented to be anomalous in autism spectrum disorder and schizophrenia (SZ), among other psychopathologies, and these—in particular SZ—are considered to be disorders of the self . Furthermore, much of the recent evidence suggesting deficitary sensory processing in psychopathology is highlighting the presence of either weak or inflexible priors .…”
Section: Leveraging the Plastic Body And Translational Opportunitymentioning
confidence: 99%